Very high energy γ-ray emission from two blazars of unknown redshift and upper limits on their distance. Issue 4 (23rd April 2020) - Abdalla, H; Adam, R; Aharonian, F; Ait Benkhali, F; Angüner, E O; Arakawa, M; Arcaro, C; Armand, C; Armstrong, T; Ashkar, H; Backes, M; Baghmanyan, V; et al.
ABSTRACT: We report on the detection of very high energy (VHE; E > 100 GeV) γ-ray emission from the BL Lac objects KUV 00311−1938 and PKS 1440−389 with the High Energy Stereoscopic System (H.E.S.S. ). H.E.S.S. observations were accompanied or preceded by multiwavelength observations with Fermi /LAT, XRT and UVOT onboard the Swift satellite, and ATOM. Based on an extrapolation of the Fermi /LAT spectrum towards the VHE γ-ray regime, we deduce a 95 per cent confidence level upper limit on the unknown redshift of KUV 00311−1938 of $z$ < 0.98 and of PKS 1440−389 of $z$ < 0.53. When combined with previous spectroscopy results, the redshift of KUV 00311−1938 is constrained to 0.51 ≤ $z$ < 0.98 and of PKS 1440−389 to 0.14 ⪅ $z$ < 0.53.